Effects of increasing CA:P ratio in diets containing phytase on finishing pig growth performance - S M Hanni; M R Barker; N Z Frantz; C N Groesbeck; T P Keegan; C W Hastad; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2003)
A total of 144 finishing pigs (72 barrows and 72 gilts, initially 85 lb) were used to determine the effects of calcium to total phosphorus (Ca:P) ratio in diets containing phytase on growth performance, carcass characteristics, and bone ash percentage. Pigs were housed in an environmentally regulated finishing building with two pigs per pen and six pens per sex per treatment in a randomized complete block design. Pigs were blocked by initial weight and sex, and then allotted to one of six dietary treatments. The dietary treatments were corn-soybean meal-based diets fed in three phases. In each phase, diets consisted of a 0.75:1; 1:1; 1.25:1; 1.5:1, and 2:1 Ca:P ratio. A sixth treatment group was a diet containing 77% of the total P as the other treatment diets. Diets were formulated to contain 0.44%, 0.39%, and 0.34% total phosphorus and 0.15%, 0.12%, and 0.07% available phosphorus from d 0 to 28, 28 to 57, and 57 to 76, respectively. All diets contained 0.05% phytase, providing 300 FTU/kg in order to achieve equivalent available phosphorus values of 0.23%, 0.19%, and 0.15%. For the overall experiment, increasing Ca:P ratio decreased (linear, P<0.03) ADG and F/G. However, the greatest decrease in ADG and F/G was observed when Ca:P ratio increased from 1.5:1 to 2:1. Daily feed intake was not affected by Ca:P ratio. There was no difference in backfat thickness for pigs fed Ca:P ratios between 0.75:1 and 2.0:1 (P<0.17). However, pigs fed the negative control diet had reduced backfat thickness (P<0.05) compared to the other pigs. Bone ash percentage was not affected (P<0.23) by Ca:P ratio. These results suggest that in finishing diets containing 300 FTU/kg phytase, a Ca:P ratio greater then 1.5:1 will decrease ADG and ADFI.; Swine Day, 2003, Kansas State University, Manhattan, KS, 2003
Keywords: Swine day; 2003; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 920; Kansas Agricultural Experiment Station contribution; no. 04-120-S; Calcium; Phosphorus; Phytase; Finishing pigs; Swine